2018
DOI: 10.20944/preprints201806.0157.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Static-Loop-Current Attack against the KLJN Secure Key Exchange System

Abstract: A new attack against the Kirchhoff-Law-Johnson-Noise (KLJN) secure key distribution system is studied with unknown parasitic DC-voltage sources at both Alice's and Bob's ends. This paper is the generalization of our earlier investigation with a single-end parasitic source. Under the assumption that Eve does not know the values of the parasitic sources, a new attack, utilizing the current generated by the parasitic dc-voltage sources, is introduced. The attack is mathematically analyzed and demonstrated by comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 22 publications
(63 reference statements)
0
21
0
Order By: Relevance
“…Several potential security vulnerabilities of the KLJN system have been addressed in previous research [4,42,[73][74][75][76][77][78][79][80][81][82][83][84][85][86]. However, in each case it was shown that these attacks do not compromise the unconditional security of the KLJN scheme because, similarly to quantum encryption, the information leak can be eliminated by defense hardware and privacy amplification.…”
Section: { } M a Bmentioning
confidence: 99%
See 4 more Smart Citations
“…Several potential security vulnerabilities of the KLJN system have been addressed in previous research [4,42,[73][74][75][76][77][78][79][80][81][82][83][84][85][86]. However, in each case it was shown that these attacks do not compromise the unconditional security of the KLJN scheme because, similarly to quantum encryption, the information leak can be eliminated by defense hardware and privacy amplification.…”
Section: { } M a Bmentioning
confidence: 99%
“…However, if there is, that serves with potential information leak toward Eve. Papers [75,76] explored passive attack schemes that exploit the existence of parasitic DC sources, which is typical in digital circuitry through nonzero ground resistance (ground loop effects). In [75] the parasitic DC source is located at one end of the information channel while in [76] DC sources are located at both ends.…”
Section: Loop Current Attacksmentioning
confidence: 99%
See 3 more Smart Citations